Chemical composition and mass closure for airborne particulate matter in bogotá (2010)
Particulate matter, measured as PM10, is the most concerning airborne pollutant in Bogotá. Determining its chemical com- position is important for understanding its potential effects and to estimate various sources’ contribution to such pollution. This paper gives the results of characterizing the ionic species, carbonaceous material, metals and crustal elements present in airborne PM10 in Bogotá. An ion charge balance and mass reconstruction were done for determining consistency between chemical characterization and gravimetric PM10. The composition was different in each area; however, the fractions contributing most to PM10 were crustal, 37% to 42% was related to fugitive and suspended dust, 12% to 11% was related to carbonaceus fractions, 43% to elemental carbon, 34% for organic matter and 5% to 8% for ionic fractions.